Family support with self-care management in hypertension patients: A correlation study - Hikayati Hikayati; Mutia Nadra Maulida; Vike Listari (Malahayati International Journal of Nursing and Health Science, 2025)
Background: Self-care management can be very helpful in reducing the risk of hypertension complications, but the fact is that there are still many people with hypertension who are currently unable to do self-care management. Many patients are not routine in controlling blood pressure, do not take medication regularly, and do not apply a healthy lifestyle. One of the success factors of hypertension self-care management is family support. Purpose: to determine the relationship between family support and self-care management in patients with hypertension. Method: This type of research is quantitative research with a cross sectional design. The sample in this study amounted to 60 respondents who were selected using the nonprobability sampling method with purposive sampling techniques. The data was tested using the spearman rank correlation statistical test. Results: The results of the study found that there was a significant relationship between family support and self-care management in patients with hypertension in the working area of the Kenten Health Center Palembang City with a p-value of 0.000 (p-value < 0.05). The correlation coefficient between family support and self-care management is 0.459 (quite strong). Conclusion: Family support significantly influences sufferers in improving self-care management to maintain their health status.